Pengaruh Rebranding Terhadap Brand Image Taman Impian Jaya Ancol - Uus Khusnul Khotimah; Jamiati KN (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Taman Impian Jaya Ancol has lost around 6 million visitors over the past three years due to the co-19 pandemic, this requires companies to think about the right strategy to exist and survive during the co-19 pandemic. One of the strategies implemented by Taman Impian Jaya Ancol is rebranding. By rebranding a company can change its image through adopting a name or changing a name that is more representative and distinguishes itself from its competitors. This study aims to determine and measure the effect of rebranding on the brand image of Taman Impian Jaya Ancol. Using a survey method with a quantitative approach. This research involved 343 followers of the Instagram account @Ancoltamanimpian as a population. The sample consists of 77 people who will answer, and are taken by the Slovin formula. The probability sampling method with simple random sampling technique is the sampling technique in this study. The data collection method is a questionnaire, and data analysis is a simple linear regression. The results showed that the correlation coefficient value of R for rebranding was 0.573 indicating that rebranding had a moderate or moderate effect on the brand image of Taman Impian Jaya Ancol. Meanwhile, the coefficient of determination has an R-square value of 0.329 indicating that the X variable, namely rebranding, influences the Y variable of the Taman Impian Jaya Ancol brand image by 32.1%, and the remaining 67.1% is influenced by other factors or variables that not included in the study. There is an influence between rebranding and the brand image of Taman Impian Jaya Ancol, as shown by the hypothesis test, namely H_1 is accepted and ã€–Hã€—_0 is rejected where t_count (6.054) > t_table (1.992).